2022
DOI: 10.1002/jctb.7154
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of organobentonite by microwave‐assisted heating and its adsorption property for phenol

Abstract: BACKGROUND: The adsorption removal of phenol onto bentonite that was prepared by the traditional hydrothermal method has been widely studied; especially, surfactant-modified bentonite has achieved an exclusive position on effective removal to phenol. However, the adsorption performance of the bentonite functionalized by double-carbon chain surfactants in a microwave field for phenol is relatively low. The study on the fabrication of organobentonite by microwave-assistance to remove organic pollutants still nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…It was found that the CO 2 adsorption process was physical, exothermic, and spontaneous at lower temperature. Another adsorbent organobentonite was fabricated by Ye et al 2 by microwave‐assisted heating to adsorb phenol. They found that the adsorption performance of bentonite was enhanced after functionalizing with organic modifier Dihexadecyldimethylammonium Bromide (D1621).…”
mentioning
confidence: 99%
“…It was found that the CO 2 adsorption process was physical, exothermic, and spontaneous at lower temperature. Another adsorbent organobentonite was fabricated by Ye et al 2 by microwave‐assisted heating to adsorb phenol. They found that the adsorption performance of bentonite was enhanced after functionalizing with organic modifier Dihexadecyldimethylammonium Bromide (D1621).…”
mentioning
confidence: 99%